Innovative Learning Approaches for Medical Students: A Comparative Analysis of Hybrid Learning vs Conventional Lectures - Mayasari, Dyah Samti; Hafizhah, Bidhari; Abdullah, Hafidz; Hasana, Shofuro; Alfina, Saski Yasmin; Fatimah, Vita Arfiana Nurul; Solikhah, Hana Maryam; Kokasih, Orisativa; Gharini, Putrika Prastuti Ratna (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2025)
Introduction: With the rapid progress of technology, learning approaches have increasingly moved online, including the method for learning electrocardiography (ECG). ECG interpretation is a core skill for physicians, especially in emergency settings. Massive Open Online Courses (MOOCs) provide a flexible and complementary learning method that complements traditional classroom instruction. This study aims to evaluate the effectiveness of MOOCs as a complementary learning method and compare that with conventional learning in enhancing ECG knowledge among second-year preclinical students.Methods: A prospective cross-sectional study with consecutive sampling was conducted to recruit participants. They were divided into a control group (conventional lectures) and an intervention group (using MOOC as a complementary method). All participants are required to complete pre-test and post-test questionnaires, as well as evaluations after each module. This study compared learning gain scores between traditional and hybrid learning methods.Results: Of the 258 participants registered, 160 students completed the learning modules, including the post-test. The majority of participants were female, all under 25 years old, and had been in medical education for 1.5 to 2 years. Overall, the gain score achieved was 2.03 for traditional and 2.75 for hybrid. While the topics of electrolyte imbalance and heart enlargement showed increasing scores, arrhythmia and ECG in ischemia and infarction showed lower scores for the hybrid method. Not all registered participants completed the course; the main factor motivating participants to complete the course was gaining knowledge (80.00%). Conclusion: Hybrid ECG learning using online media, such as video lectures and mini-quizzes, improves interpretation skills more effectively than traditional methods by boosting engagement and knowledge retention. To further enhance learning, integrating artificial intelligence-driven reminders and monitoring can improve completion rates, and continuous updates to the curriculum are necessary to strengthen medical students' ECG competence.